2022
DOI: 10.3390/su14105761
|View full text |Cite
|
Sign up to set email alerts
|

What Determines the Shadow Economy? An Extreme Bounds Analysis

Abstract: The purpose of this paper was to identify the leading causes determining the shadow economy at the global level. The empirical analysis used was the Sala-i-Martin version of extreme bounds analysis (EBA) applied to a cross-sectional sample of 132 countries. The results suggested that the quality of institutions is the primary determinant of the shadow economy. The results showed that only four out of six factors of the quality of institutions proved to be robust determining factors of the shadow economy; they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…Our empirical findings reinforce the widely accepted concept that unregulated shadow economic activities serve as a breeding ground for terrorism, particularly in regions characterized by weak or absent formal economic and political infrastructures. Notably, our research emphasizes that an expansion of the shadow economy in developing nations relates to a reduction in terrorism control (Abu Alfoul et al, 2022;Hutchinson & O'Malley, 2007;Jadoon & Milton, 2022;Pieth, 2017;Schneider & Buehn, 2018). Moreover, our results verify the concentration of terrorist activities in regions marked by ethnic and religious conflicts.…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 72%
See 1 more Smart Citation
“…Our empirical findings reinforce the widely accepted concept that unregulated shadow economic activities serve as a breeding ground for terrorism, particularly in regions characterized by weak or absent formal economic and political infrastructures. Notably, our research emphasizes that an expansion of the shadow economy in developing nations relates to a reduction in terrorism control (Abu Alfoul et al, 2022;Hutchinson & O'Malley, 2007;Jadoon & Milton, 2022;Pieth, 2017;Schneider & Buehn, 2018). Moreover, our results verify the concentration of terrorist activities in regions marked by ethnic and religious conflicts.…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 72%
“…Our empirical findings support the maxim that unregulated shadow economic activities contribute to the sustenance and proliferation of terrorism, particularly in regions where formal economic and political structures are weak or absent. Empirical findings of our research indicate that an increase in the shadow economy in developing countries reduces the control of terrorism (Abu Alfoul et al, 2022;Hutchinson & O'Malley, 2007;Jadoon & Milton, 2022;Pieth, 2017;Schneider & Buehn, 2018). Our results also conventionally demonstrated that all terroristic acts are concentrated in locations where ethnic and religious conflicts predominate.…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 65%
“…or when legal activities are carried out under illegal conditions. The latter category includes strategies such as undeclared employment, non-declaration of employees, under-invoicing, smuggling, corruption and fraudulent ac-counting (Abu Alfoul et al, 2022;Torgler and Schneider, 2009). These underground economy activities represent significant losses for the tax authorities.…”
Section: The Underground Economymentioning
confidence: 99%